STUDI POTENSI BIOMASSA DAN KARBON PADA TEGAKAN HUTAN DI KPHP MODEL SUNGAI MERAKAI KABUPATEN SINTANG PROVINSI KALIMANTAN BARAT - Prahara, Agust; Hardiansyah, Gusti; Widhanarto, Ganjar Oki (Universitas Tanjungpura, 2015)
The purpose of this research was to estimate biomass and carbon stored in the forest unit management of KPHP to know its potency to adsorb atmospheric CO2 gas and comply with standart from IPCC recomendationÂ in the Model Forest Production Management Unit S. Merakai Sintang Regency. Method of inventory is â€œnon destructive sampling at Above Ground Baiomass poolâ€, placement stand the sample plot is purposive sampling based on 2012 Â land cover image of Landsat ETM 7+ stratificated year 2012 BPKH Wilayah III Pontianak dided. KPHP Model S. Merakai Sintang RegencyÂ was founded by Minister of forestry decree number Â : SK. 791/MENHUT-II/2009, Desember, 7th, 2009. The result of this research four class sample of land cover: Primary Forest with the average biomass 363,82 ton /Ha and carbon stored 234,54 ton C/Ha, Secondary Forest with the average biomass 499,02 ton/Ha and carbon stored 171,00 ton C/Ha, Secondary Swamp Forest with the average biomass 451,91 ton /Ha and carbon stored 212,40 ton C/Ha, bush shrub with the average biomass 17,79 ton/Ha and carbon stored 8,63 ton C/Ha. Key Words : Biomass, Carbon, KPHP Model S. Merakai